Literasi Pemanfaatan Aplikasi Keuangan Digital Bukukas Pada Umkm Di Kota Sampit, Kalimantan Tengah. - Rahmad Kurniawan; Jefry Tarantang; Wahyu Akbar; Sofyan Hakim; Enriko Tedja Sukmana; Riza Hafizi (Jurnal Pengabdian Masyarakat Formosa, 2022)
In the current digital era, there are still many MSMEs that do manual recording, especially in Sampit City. The importance of digital financial literacy through bookkeeping applications for MSMEs can help them record their financial transactions and make it easier to recap the sales of products sold through the Cash Book application. The purpose of community service for MSMEs is to record financial transactions using the BukuKas application simply. The method used is service learning, starting from the preparation stage, dedication stage and reflection. As a result of this activity, MSME actors can use the BukuKas application, can operate transactions in BukuKas, and can find out the cost of goods sold, make financial records and make financial reports.